The branches of the arteria celiaca in the porcupine (Hystrix cristata) - Atalar, O; Yilmaz, S (Czech Academy Agricultural Sciences, 2004)
This study is aimed at an investigation of the A. celiaca and its branches in the porcupine. Nine adult porcupines (5 males, 4 females) were injected a coloured latex mixture from the aortic arch for the demonstration of the arteria celiaca. The results indicated that the A. celiaca gave off the A. phrenica caudalis after approximately 1 cm from its origin. The A. celiaca was divided into two branches as the A. lienalis and A. hepatica. The A. hepatica was a continuity of celiac artery. The ramus pancreaticus, which was the most important artery for pancreas vascularization, arose from the A. lienalis. The ramus gastrolienalis and the Aa. gastricae breves were observed. The first branch of the A. hepatica was the A. gastrica dextra. The thickest branch of hepatic artery was the A. gastrica sinistra that separated two branches: the ramus visceralis and the ramus parietalis. In summary, in the present study the branches of the A. celiaca in porcupines were studied for the first time. The results of this study may contribute to the data in this area of science.
Keywords: arteries; Hystrix cristata; celiac artery; porcupine